1993
DOI: 10.1159/000107319
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Neurochemical Findings in Non-Alzheimer Dementia due to Lobar Atrophy

Abstract: Non-Alzheimer''s dementia due to lobar atrophy had choline acetyltransferase activities comparable with control rather than Alzheimer''s disease values, based on 3 autopsy proven cases on Pick''s disease and biopsies from 3 examples of dementia of frontal lobe type. Muscarinic cholinergic receptors were relatively spared only in Alzheimer''s disease. Serotonin receptors were markedly reduced (based on Pick cases) whereas measures that reflected presynaptic serotonergic activity were either not affected or incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
3

Year Published

1996
1996
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 20 publications
2
41
0
3
Order By: Relevance
“…14,17,18 This has been demonstrated by a recent PET study that demonstrated decreased 5-HT2A receptors in the orbitofrontal, frontal medial, and cingulate cortices of patients, 19 deficiencies of nonspecific serotonin binding, 14 decreased 5-HT1A and 5-HT2A receptors, 17 and decreased LSD 5-HT receptor binding. 18 Three experiments have shown intact or increased imipramine binding, and other measures of presynaptic serotonergic activity, in FTD. 14,15,18 However, one study showed neuron loss in the raphe nuclei in patients with FTD.…”
Section: Mechanism Reviewmentioning
confidence: 79%
See 2 more Smart Citations
“…14,17,18 This has been demonstrated by a recent PET study that demonstrated decreased 5-HT2A receptors in the orbitofrontal, frontal medial, and cingulate cortices of patients, 19 deficiencies of nonspecific serotonin binding, 14 decreased 5-HT1A and 5-HT2A receptors, 17 and decreased LSD 5-HT receptor binding. 18 Three experiments have shown intact or increased imipramine binding, and other measures of presynaptic serotonergic activity, in FTD. 14,15,18 However, one study showed neuron loss in the raphe nuclei in patients with FTD.…”
Section: Mechanism Reviewmentioning
confidence: 79%
“…This includes autopsy, [14][15][16][17][18] imaging, 19 and CSF studies. 20 Some CSF studies have failed to show a significant decrease in CSF 5-hydroxyindoleacetic acid (5-HIAA, a serotonin metabolite) 18,21,22 but two of these studies showed nonsignificant trends toward decreased CSF 5-HIAA in patients with FTD. 21,22 This serotonergic deficit appears to be more postsynaptic than presynaptic.…”
Section: Mechanism Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…18,26 As opposed to what occurs in other primary dementias, such as in AD and in dementia with Lewy bodies, neurochemical studies did not show changes in the cholinergic system in FTD. 27 Therefore, the acetylcholinesterase inhibitors used in the treatment of these primary dementias did not benefit patients with FTD. 2,28,29 Changes in the serotoninergic system are found in different clinical conditions that manifest apathy/depression or disinhibition/impulsiveness.…”
Section: Pharmacological Therapy Of Ftdmentioning
confidence: 99%
“…27 Behavioral disorders, particularly disinhibition and aggressiveness, that expose the patient or their caretakers to risks, may be controlled with dopaminergic antagonists or antipsychotic drugs. 28,29 In this case, the current tendency is to preferentially use the atypical antipsychotic drugs.…”
Section: Pharmacological Therapy Of Ftdmentioning
confidence: 99%